Survey on the eating behavior of first-year medical students at University of Medicine and Pharmacy, Hue University - Tran, Thi Tao; Nguyen, Ngo Bao Khuyen; Hoang, Thi Bach Yen; Nguyen, Thi Thanh Nhan; Nguyen, Thi Thanh Thao; Ho, Uyen Phuong; Bui, Le Thao Phuong; Tran, Quoc Nhat Truong; Pham, Le Minh; Phan, Anh Kiet; Ngo, Ngoc Hung; Tran, Thi Quy; et al. (Tạp chí Y Dược Huế, 2025)
Background: Nutrition is closely related to human health. Unhealthy diet increases the risk of non-communicable diseases such as cardiovascular disease, diabetes, hypertension, overweight and obesity. Changing eating habits and unhealthy behaviors can last a long time and affect the future. Objectives: (1) To describe the eating behaviors of first-year medical students at University of Medicine and Pharmacy, Hue University, (2) To identify some factors related to the eating behaviors of these students. Methods: A cross-sectional study was conducted on 312 students at Hue University of Medicine and Pharmacy from July 2023 to August 2024. Data were collected by direct interview based on a structured questionnaire. We used a multivariate logistic regression model to identify factors associated with students’ eating behavior. Results: There was 58.3% of students with poor behavior. Some factors associated with students’ eating behaviors were sex, monthly allowance, physical activity, bedtime, time spent for using the Internet, desire to change diet, with a significance level of p<0.05. Conclusion: Medical students have a high proportion of poor eating behavior. Our study emphasizes the importance of getting more than six hours of sleep and reducing internet use among students, while also providing education on healthy diets to encourage positive changes in eating habits. Additionally, encouraging students to engage in physical activities contributes to maintaining a healthy lifestyle.